Amomum xizangense (Zingiberaceae), a new species from Xizang, China - Fu, Lin; Huang, Jian-Ping; Wu, Xing; Du, Zhi-Jian; Lin, Ling; Ye, Yu-Shi (Phytotaxa, 2021)
Amomum xizangense (Zingiberaceae), a new species from Xizang, China, is described and illustrated. It is similar to A. maximum and A. subcapitatum, but differs in having purple-red leaf sheath, purple-red or reddish-green petiole, lamina with purple-red midvein, persistent bracts and bracteoles, yellowish-white calyx, yellowish corolla, yellow anther with trilobed and yellow crest and globose fruit.